Mergers and Acquisitions as a Strategic Corporate Restructuring Agenda: Synergies, Risks, and Firm Value - Mizvi, Adhiya; Sianturi, Agusman; Mukhtaruddin , Mukhtaruddin (Jurnal Locus Penelitian dan Pengabdian, 2026)
Background: This study examines the strategic role of Mergers and Acquisitions (M&A) as a corporate restructuring mechanism aimed at generating operational and financial synergies while influencing firm value in the context of global market volatility. Objectives: The primary objective of this study is to provide a comprehensive understanding of the impact of M&A on firm value, by identifying key factors influencing the success or failure of M&A transactions. Specifically, the study aims to explore how synergies are realized, how key risks are managed, and the role of contextual factors in determining M&A outcomes. Methods: Using a Systematic Literature Review (SLR) approach guided by the PRISMA protocol, this research synthesized 75 empirical and conceptual articles indexed in Scopus and SINTA, published between 2020 and 2026. Results: The findings indicate that the effect of M&A on firm value is heterogeneous and highly context-dependent, with outcomes ranging from substantial value creation to persistent value destruction. The success of M&A transactions largely depends on the effective realization of synergies and the management of key risks, including overpayment, post-merger integration failures, agency conflicts, cultural differences, and regulatory complexities in cross- border deals. Theoretically, this study integrates major perspectives, such as the Resource-Based View (RBV), Efficiency Theory, Agency Theory, and Institutional Theory, to provide a multidimensional explanation of restructuring outcomes. Conclusion: The study offers a comprehensive framework to assist managers, investors, and policymakers in designing more sustainable and strategically aligned M&A decisions by balancing synergy objectives with robust risk management and governance mechanisms.